Apoptotic genes expression in Î³-irradiated rats treated with wheat germ oil, zinc and /or bone marrow - Mohamed, Mona; Ahmed, Mevat (International Journal of Basic and Applied Sciences, 2014)
Background: Liver inflammation or injury is a hallmark of ionizing radiation. Natural radio-protectors are found in plant materials such as wheat germ oil, in addition to other dietary antioxidants, such as zinc.Objectives: The present study was designed to evaluate the amelioration of mRNA levels of Bax, bcl-2, p53 and caspase-3 in the liver of ?-irradiated rats treated with wheat germ oil, zinc sulphate and/or bone marrow.Methods: Animals were exposed to an acute single dose of 5Gy whole body irradiation of gamma radiation from Gamma-cell 40 (cesium- 137) source. RNA was extracted from hepatic tissue homogenate and reverse transcribed into cDNA using RT-PCR kit.Results: A significant elevation was observed in hepatic level of mRNA of Bax and caspase 3, while levels of bcl-2 and p53 mRNA were decreased in irradiated rats as compared to control. A combination of bone marrow and wheat germ oil caused a significant reductions in hepatic mRNA levels of Bax and caspase 3 (3.1 and 1.5-fold, respectively), associated with a significant comparable elevation in hepatic mRNA level of p53 (2.7-fold), compared to the irradiated group.Conclusions: Results obtained from this study suggest that supplementation of wheat germ oil with either BM or zinc to irradiated rats down regulates the proapoptotic genes.Keywords: Bax, Bcl-2, Caspase-3, P53.